Effect of Aging on mechanical behaviour of ADC12-Fly Ash particulate composite. (2017) - Tiwari, Sumit Kumar; Soni, Sanjay; Rana, R.S.; Singh, Alok
Abstract: The present work deals with Al alloy-fly ash particulate composite developed by reinforcing 6 wt% fly ash particles in the Al Alloy (ADC 12) matrix. The effect of heat treatment has been studied on the mechanical properties of different composites. The mechanical properties such as the tensile strength, hardness and impact strength of the composites in as cast and heat treated condition were studied in order to achieve the maximum properties. Composites with fly ash with ADC-12 as reinforcement are likely to overcome the cost barrier as well as the different physical and mechanical properties for widely used in the automotive and space craft applications. In- Al alloy composites containing 6% weight fractions of particles of Fly ash mixed by stir carting method and the particles were distributed evenly in the matrix of the composites as per the experiments done. For increasing wet ability, Mg also added (0.5%) by that means it decreases the surface tension of the fly ash. For better mixing of all materials, there is an arrangement of stirrer which stirs the melted composite material. Reinforcing Fly Ash (60-100μm) particles in aluminium alloy tends to reduce the tensile properties as during tensile deformation the soft aluminium alloy will elongate and the Fly Ash particles which are very hard are not deformed at the same rate as the aluminium alloy does. It is observed that there is a reduction in impact strength of ADC12-Fly ash composite as compared to the aluminium alloy. Also there is an increase in impact strength due to aging, maximum at 130°C in alloy and at 150° in composite. Hardness of composite improved as compared to the alloy. Also there is an improvement in hardness due to aging, maximum at 175°C.